ISOLATION AND CHARACTERIZATION OF THE AGROBACTERIUM TUMEFACIENS FROM ALMOND NURSERIES IN CHLEF REGION IN WESTERN ALGERIA - Benali Setti; Mohamed Bencheikh (European Scientific Journal, ESJ, 2013)
Crown gall is one of the destructive diseases and occurs worldwide. It is considered to be a disease of great economic importance in almond and other stone fruit tree nurseries due to the extensive losses. Based on their morphological characteristics on MacConkey medium and YMA medium, 10 isolates were selected on colonies of these isolates after 48 h at 28°C were circular, convex with smooth, translucent and easily suspended in water. The bacterial cells were rod shaped with rounded ends and were either single or in pairs. The isolates were Gram negative, the optimum growth was between 25 and 27°C.All strains are positive for mobility, catalase, oxydase. On the other hand, these isolates had all oxidized the lactose to 3-ketolactose. On the other hand, all Agrobacterium strains oxidized Sucrose, D-mannitol, D-sorbitol, Indol, inositol, Melibioze, D-galactose, L arabinose, Rhamnose, Amygdalin, Lactose and Glucose. Furthermore, the isolates transform also the arginin, lysin, ornithin, gelatin and starch. The pathogenic nature of the organism was confirmed by a bioassay on carrot disks. Additionally, Koch’s postulates for all isolates were also fulfilled.